How does trade, financial, social, and political globalization influence malnutrition in sub-Saharan Africa?Google drive - Shujaat Abbas (Sustainable Futures)
This study examines the influence of desegregated de facto and de jure trade globalization, financial globalization, social globalization, and political globalization on the prevalence of malnourishment in 35 sub-Saharan African countries from 2000 to 2021. The estimated results of instrumental variable quantile regression with smoothed generalized methods of moments indicate that de facto and de jure trade globalization and financial globalization improve the prevalence of malnutrition conditions in sampled countries, while de facto and de jure social globalization and political globalization aggravate it. The findings suggest that the sampled countries should prioritize domestic trade and industrial development, as well as revisit the fundamentals of globalization. Further, promotion of local culture and local cuisine can also reduce the prevalence of malnutrition.